2008
DOI: 10.1094/phyto-98-10-1118
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Common Scab-Inducing Pathogen Effects on Potato Underground Organs Via Computed Tomography Scanning

Abstract: Common scab caused by Streptomyces scabies is a major bacterial disease of potato (Solanum tuberosum). Its best known symptom is superficial lesions on the surface of progeny potato tubers, observed at harvesting. In this study, effects of S. scabies on space occupancy by underground organs and on structural complexity of root systems are investigated during growth via computed tomography (CT) scanning. Two groups of potato plants were grown in a greenhouse in middle-sized plastic pots. Using a high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Configuration parameters in our study were field of view of 18 cm in diameter combined with a zoom factor of 8, tube voltage 120 kV, and tube current 50 mA. The helical scanning mode was chosen because of its advantages in terms of image reconstruction and advanced interpolation, resulting in enhanced image precision (Han et al 2008). The reconstruction interval length was 0.1 mm and a total of 40 CT images were constructed sequentially each time, covering a distance of 4 mm in the central part of the wood sample ( Fig.…”
Section: Ct Scanningmentioning
confidence: 99%
“…Configuration parameters in our study were field of view of 18 cm in diameter combined with a zoom factor of 8, tube voltage 120 kV, and tube current 50 mA. The helical scanning mode was chosen because of its advantages in terms of image reconstruction and advanced interpolation, resulting in enhanced image precision (Han et al 2008). The reconstruction interval length was 0.1 mm and a total of 40 CT images were constructed sequentially each time, covering a distance of 4 mm in the central part of the wood sample ( Fig.…”
Section: Ct Scanningmentioning
confidence: 99%
“…Biosolid P possibly brought nutrients or physicochemical conditions that conferred an advantage to the S. scabies population or that might contribute to a better colonization of the potato seed tubers by the S. scabies. Han et al (2008) suggested that the soil population of common scab-inducing pathogens colonized seed potatoes at planting and modified root development. Alternatively, the microbial community of biosolid P might contribute to the increased level of disease by competing with S. scabies antagonistic agents that colonize soil and potato organs (Liu et al 1995) or by secreting compounds that stimulate toxin biosynthesis in S. scabies (Agbessi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…present a nice review of relevant applications [7]. Detection of the plant seed directly is usually not a primary study goal, but new methods are emerging focusing on seed-soil contact areas [45]; in some studies the seed volume is accounted for in the model parameters when estimating root volumes and detecting first-order roots [17], and plants are usually scanned after the first 7-8 days of planting [46].…”
Section: X-ray Ct Imagingmentioning
confidence: 99%
“…It has also been established that the soil substrate influences root anatomy; see, for example, Ahmed et al [11] and Rich and Watt [12]. Important influences on root development may come from abiotic stressors such as drought, salinity, and extreme temperature [13,14] not to mention biotic stressors such as pathogens [15][16][17][18]. One important biotic stressor-or helper-of particular recent interest is the rhizosphere and root-rhizosphere interactions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%